2002
DOI: 10.1093/ageing/31.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cognitive improvement after reality orientation in Alzheimer's disease

Abstract: a lower mini mental state examination and the absence of euphoric behaviour in patients with mild-to-moderate Alzheimer's disease may predict a good cognitive outcome of reality orientation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Recent research, for example, has shown that Problem-Solving Therapy may benefit patients with comorbid major depression and ED. 59,60 It is possible, therefore, that integration of RO with CBT may produce enhanced outcomes, particularly for patients with subtle deficits in cognitive functioning, such as disorientation. Another recent pilot study suggested that training in attentional processes may enhance outcomes following CBT for late-life anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research, for example, has shown that Problem-Solving Therapy may benefit patients with comorbid major depression and ED. 59,60 It is possible, therefore, that integration of RO with CBT may produce enhanced outcomes, particularly for patients with subtle deficits in cognitive functioning, such as disorientation. Another recent pilot study suggested that training in attentional processes may enhance outcomes following CBT for late-life anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…www.frontiersin.org be the target of cognitive interventions (Beck et al, 1988;Zanetti et al, 1998Zanetti et al, , 2001Zanetti et al, , 2002Clare et al, 2001;De Vreese et al, 2001;Olazaran et al, 2004Olazaran et al, , 2010Onder et al, 2005;Souchay et al, 2008).…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…However, this process is not an “all or none” phenomenon. Importantly, during the first stage of the disease process, some cognitive functions are preserved (i.e., procedural memory) and can be the target of cognitive interventions (Beck et al, 1988; Zanetti et al, 1998, 2001, 2002; Clare et al, 2001; De Vreese et al, 2001; Olazaran et al, 2004, 2010; Onder et al, 2005; Souchay et al, 2008). Moreover, several studies have demonstrated at least a modest benefit from specific interventions designed to improve functioning in select cognitive tasks.…”
Section: Memory Interventions In Mild Cognitive Impairment and Alzheimentioning
confidence: 99%